Product Domestication Process Perceived by End-Users - Andrei DUMITRESCU; Mihail PURCAREA (Communications of International Proceedings, 2021)
Product domestication is the process by which the product bought from the retailer is integrated into the household. This intricate process has been analysed in detail from a theoretical point of view, but has not been approached from the practical viewpoint of end-users. This paper presents the results of a survey on a group of students regarding various facets of the domestication process (remembering the moment of product acquisition; concern for the aesthetic assimilation of the product into the household; investment of resources - time and money - in developing a household; difference of significance between the product in store and the product in home, etc.). After the statistical analysis of the results, it was discovered that the process of product domestication is working and acknowledged by end-users, but at a moderate level in the case of the analysed population segment.
Keywords: product domestication; product appropriation; end-user point-of-view.